2021
DOI: 10.1016/j.isci.2021.103512
|View full text |Cite
|
Sign up to set email alerts
|

A transient conformation facilitates ligand binding to the adenine riboswitch

Abstract: Summary RNAs adopt various conformations to perform different functions in cells. Incapable of acquiring intermediates, the key initiations of ligand recognition in the adenine riboswitch have not been characterized. In this work, stopped-flow fluorescence was used to track structural switches in the full-length adenine riboswitch in real time. We used PLOR (position-selective labeling of RNA) to incorporate fluorophores into desired positions in the RNA. The switching sequence P1 responded to adeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…The inhibitory effect of Cy3 on the reverse transcriptase was not very significant, probably because the modification is located at the base instead of ribose in 36Cy3-riboA, leading to the reverse transcriptase not stalling exactly at the labeled site but 1 nt downstream of the labeled site (Figure C). Such a delay in an RT reaction was reported previously. , Truncated RT products were detected with a difference of 1 nt in length when using 36Cy3- and 37Cy3-riboA as templates in the RT reactions (lanes 3 and 7, Figures C, S23, Tables S21 and S22). This observation shows that precise labeling of a chosen site among consecutive nucleotides in RNAs can be achieved by SMRITI.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The inhibitory effect of Cy3 on the reverse transcriptase was not very significant, probably because the modification is located at the base instead of ribose in 36Cy3-riboA, leading to the reverse transcriptase not stalling exactly at the labeled site but 1 nt downstream of the labeled site (Figure C). Such a delay in an RT reaction was reported previously. , Truncated RT products were detected with a difference of 1 nt in length when using 36Cy3- and 37Cy3-riboA as templates in the RT reactions (lanes 3 and 7, Figures C, S23, Tables S21 and S22). This observation shows that precise labeling of a chosen site among consecutive nucleotides in RNAs can be achieved by SMRITI.…”
Section: Resultssupporting
confidence: 89%
“…Such a delay in an RT reaction was reported previously. 38,39 Truncated RT products were detected with a difference of 1 nt in length when using 36Cy3-and 37Cy3-riboA as templates in the RT reactions (lanes 3 and 7, Figures 6C, S23, Tables S21 and S22). This observation shows that precise labeling of a chosen site among consecutive nucleotides in RNAs can be achieved by SMRITI.…”
Section: ■ Resultsmentioning
confidence: 96%
“…Afterward, the capture of ligands by the flexible junction region (J12, J23, and J31) and the stabilization of P1 are particularly critical for the downstream EP of purine riboswitch to fulfill its regulatory function. Notably, the AD of purine riboswitch would appear various flexible intermediate states during the process of structural transition induced by ligand recognition 33 40 . These intermediate states are difficult to observe as a result of their high flexibility and sensitivity to the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are of great value in refining the understanding of regulation mechanisms of riboswitches, and experiments are therefore dedicated to their exploration with improved techniques. Although the structural changes in purine riboswitch and some of the important intermediate states that accompany this process have been studied experimentally to some extent, the specific roles of metal ions in these issues are still poorly understood, mainly due to the following limitations of current experimental techniques: (i) experiments based on X-ray diffraction only yield transient structures of individual intermediate states of the riboswitches, but cannot describe dynamic details of the conformational transition processes involved; (ii) while NMR and single-molecule FRET can be used to study the dynamics of biomolecules in solution and indirectly speculate on the effect of metal ions on them 36 , 39 , neither can give direct evidence of the roles of metal ions in the successive conformational transitions that occur in riboswitches 40 ; (iii) even in X-ray crystallography, it is quite difficult to identify Mg 2+ ions (most effective for stabilizing the native RNA structure) by checking residual electron density maps because they have the same number of electrons as Na + ions and water molecules 41 ; (iv) the contribution of monovalent metal ions (such as K + and Na + ) in the free or weakly bound state to the stability of the RNA structure cannot be ignored either 12 , 42 , but almost all experimental techniques are unable to assess it in detail.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the results from both approaches revealed that they agree very well and support each other, and the extracted rate constants are generally in agreement with those reported by different methods as well. 31 On top of the RNA-only system, we used SiM-KARB to investigate the ASW 30S RSU system in the presence and absence of adenine and additionally examined the effect of the ribosomal protein S1 on the binding of the 30S RSU to the riboswitch (Table 1).…”
Section: ■ Discussionmentioning
confidence: 99%